Serum IgA and IgM levels in hemochromatosis probands with HFE p.C282Y homozygosity - James C. Barton; J. Clayborn Barton; Luigi F. Bertoli; Ronald T. Acton (PLoS ONE, 2026)
Background HFE p.C282Y (rs1800562) homozygotes, including those with normal iron phenotypes, have increased risks of infection and death from infections, although serum IgA and IgM in cohorts of adults with p.C282Y homozygosity are not reported. Methods We compiled serum IgA and IgM levels at diagnosis of hemochromatosis in probands with p.C282Y homozygosity, investigated associations of IgA and IgM with clinical characteristics, blood count measures, and iron phenotypes, and compared mean IgA and IgM of probands with combined/weighted means of published adult European cohorts not selected for hemochromatosis. Results There were 73 probands (36 men, 37 women; mean age 51 ± 13 y). Fifty probands (68.5%) had human leukocyte antigen (HLA)-A*03. Mean IgA ± standard deviation [95% confidence interval] was 2.11 ± 1.06 g/L [1.87, 2.35]. Mean IgM was 1.11 ± 0.75 g/L [0.94, 1.28]. IgM was inversely associated with age (Pearson’s r 73 = –0.2733; p = 0.019). A multiple regression on IgA revealed no significant association with other characteristics. A regression on IgM revealed one positive association (daily alcohol intake; p = 0.036) and one negative association (age; p = 0.016). Mean IgA of male and female probands and corresponding mean IgA of Europeans in two cohorts (918 men, 458 women) did not differ significantly. Mean IgM of probands was lower than the mean IgM of Europeans in four cohorts (men 1.03 ± 0.84 g/L vs. 1.35 ± 0.55 g/L (n = 1084), respectively (p < 0.001); women 1.18 ± 0.67 g/L vs. 1.57 ± 0.68 g/L (n = 622), respectively (p < 0.001)). Conclusions There is no significant association of serum IgA in HFE p.C282Y homozygotes with the clinical and laboratory characteristics we studied. Serum IgM levels are positively associated with daily alcohol intake, are inversely associated with age, and are lower than those of Europeans not selected for hemochromatosis.